INSTRUMEN ASESMEN BAHASA INGGRIS SMP PESERTA PPP BAHASA INGGRIS UNIVERSITAS NEGERI SURABAYA - Fauris Fauris (EDU-KATA, 2019)
The purpose of research is how participants of teacher training program increase their ability to compose assessment instruments in level of planning, developing, and implementing. It relates with the research question: how do the participants of tecaher training program increase their ability to compose assessment instruments in level of planning, developing, and implementing? This research is conducted to the students of English Department of Faculty of Language and Arts the State University of Surabaya. It is expected to increase their ability in composing English assessment instruments in junior high school level. Descriptive qualitative research is implemented.